2021
DOI: 10.1016/s1474-4422(20)30494-4
|View full text |Cite
|
Sign up to set email alerts
|

Second intravenous immunoglobulin dose in patients with Guillain-Barré syndrome with poor prognosis (SID-GBS): a double-blind, randomised, placebo-controlled trial

Abstract: Second intravenous immunoglobulin dose in patients with Guillain-Barre syndrome with poor prognosis (SID-GBS): a double-blind, randomised, placebo-controlled trial. Lancet Neurology, 20(4), 275-283.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 33 publications
1
23
0
2
Order By: Relevance
“…41,42 This was indicated by a recent 2021 randomized controlled trial, which reported a second IVIG dose was not significantly associated with any significant improvements in patients with severe GBS and it can negatively impact the prognosis by inducing some adverse events. 43 The same results were also previously reported by an observational study by Verboon et al which showed that second IVIG doses could not significantly enhance the prognosis of poor GBS. 44 Although previous investigations have approached the efficacy of some other management modalities, none of these approaches have been proven to be significantly efficacious as compared to plasma exchange and IVIG.…”
Section: Managementsupporting
confidence: 82%
“…41,42 This was indicated by a recent 2021 randomized controlled trial, which reported a second IVIG dose was not significantly associated with any significant improvements in patients with severe GBS and it can negatively impact the prognosis by inducing some adverse events. 43 The same results were also previously reported by an observational study by Verboon et al which showed that second IVIG doses could not significantly enhance the prognosis of poor GBS. 44 Although previous investigations have approached the efficacy of some other management modalities, none of these approaches have been proven to be significantly efficacious as compared to plasma exchange and IVIG.…”
Section: Managementsupporting
confidence: 82%
“…Nevertheless, our data argue against a strong effect of multiple treatments on short-term outcome. To investigate whether repeated treatments had negative effects due to adverse events—as suggested by the recent randomized study for IVIg 8 —was beyond the scope of our study. However, given the comparable rate of side effects of IVIg and PE it is currently hard to justify any sequential treatment in patients with GBS, regardless of clinical severity or assumed prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A second IVIg course after PE or IVIg has not been associated with an additional benefit regarding outcome in non-randomized studies 6 , 7 . Recently, a placebo-controlled, randomized trial in patients with poor prognosis also failed to show a treatment effect of a second IVIg course and led to a higher number of adverse events 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the recently published SID-GBS study, a randomized, double-blind, placebo-controlled trial, did not provide evidence that GBS patients with a poor prognosis benefit from a second IVIg course and showed that patients given a second IVIg course had more serious adverse effects. Second IVIg courses should not be administered in GBS patients with poor prognosis [ 138 ].…”
Section: Guillain-barré Syndromementioning
confidence: 99%